Writing Disabilities and Reading Disabilities in Elementary School Students: Rates of Co-Occurrence and Cognitive Burden. (February 2016) - Costa, Lara-Jeane C.; Edwards, Crystal N.; Hooper, Stephen R.
This longitudinal study was conducted to determine (a) the rate of co-occurrence of reading disabilities (RDs) in a writing disability (WD) population of students followed from first grade to fourth grade and (b) the cognitive burden that is assumed by having a WD and a RD (WD + RD). The sample included 137 first-grade students from a single school district who initially were placed into three groups based on the Wechsler Individual Achievement Test–Second Edition (WIAT-II) Written Expression subtest: Typically Developing (TD; n = 83), WD-Only ( n = 38), and WD + RD ( n = 16). Results indicated that the rate of a WD + RD increased with advancing grades, ranging from 30% in first grade to 47% in fourth grade. This increase was secondary to the instability of group membership across all three groups. The number of students with a WD + RD remained relatively constant over the 4 years, with about 50% of first-grade students with a WD + RD continuing to manifest this co-occurrence through the fourth grade. There was increased cognitive burden for the students in the WD + RD group across the four grades in language and executive dysfunctions. Along with the use of progress monitoring strategies for both reading and writing in the early grades, these findings suggest the importance of assessing the cognitive underpinnings for students with a WD + RD.